N-alkylated polydithiocarbamates derived from thiocarbonyl fluoride as macro-photoiniferters for living 3D printing - Pengfei Ruan; Haonan Xiang; Wenbin Yi; Jieping Wang (Nature Communications)
Abstract Polydithiocarbamates represent a unique class of sulfur-containing polymers possessing advanced functionalities. However, their structural and functional exploration has been limited by significant synthetic challenges. Existing methods primarily yield polydithiocarbamates incorporating secondary amides within the polymer backbone. Herein, we report a versatile synthetic strategy enabling access to previously inaccessible N-alkylated polydithiocarbamates. Utilizing secondary diamines, dithiols, and thiocarbonyl fluoride, we efficiently synthesize these polymers with diverse structures. Notably, these materials function as superior macro-photoiniferters for fully open-to-air 3D printing, exhibiting enhanced resolution and outperforming small-molecule analogues. Critically, the dormant dithiocarbamate functionalities within the 3D-printed structures can be reactivated for iterative modifications, demonstrating the potential for living 3D printing. More interestingly, the unique capability of the macro-photoiniferter (P1) to eliminate stair-stepping layer patterns without requiring printer modifications or additional pre- or post-processing steps represents a simple yet powerful approach that could substantially enhance the flexibility and output quality of DLP 3D printing. We demonstrate that thiocarbonyl fluoride is a key reagent for the controlled synthesis of sulfur-containing polymers. We anticipate that our polydithiocarbamate-based macro-photoiniferters will drive advancements in diverse fields, including biomedicine, energy, and materials science.